MAYBE Initial complexity problem: 1: T: (1, 1) f0(a, b, c) -> f1(0, b, c) (?, 1) f1(a, b, c) -> f1(a, b - 1, d) [ b >= 1 ] (?, 1) f1(a, b, c) -> f4(a, b, d) [ 0 >= b ] (?, 1) f4(a, b, c) -> f4(1, b, d) start location: f0 leaf cost: 0 A polynomial rank function with Pol(f0) = 1 Pol(f1) = 1 Pol(f4) = 0 orients all transitions weakly and the transition f1(a, b, c) -> f4(a, b, d) [ 0 >= b ] strictly and produces the following problem: 2: T: (1, 1) f0(a, b, c) -> f1(0, b, c) (?, 1) f1(a, b, c) -> f1(a, b - 1, d) [ b >= 1 ] (1, 1) f1(a, b, c) -> f4(a, b, d) [ 0 >= b ] (?, 1) f4(a, b, c) -> f4(1, b, d) start location: f0 leaf cost: 0 A polynomial rank function with Pol(f0) = V_2 Pol(f1) = V_2 Pol(f4) = V_2 orients all transitions weakly and the transition f1(a, b, c) -> f1(a, b - 1, d) [ b >= 1 ] strictly and produces the following problem: 3: T: (1, 1) f0(a, b, c) -> f1(0, b, c) (b, 1) f1(a, b, c) -> f1(a, b - 1, d) [ b >= 1 ] (1, 1) f1(a, b, c) -> f4(a, b, d) [ 0 >= b ] (?, 1) f4(a, b, c) -> f4(1, b, d) start location: f0 leaf cost: 0 Applied AI with 'oct' on problem 3 to obtain the following invariants: For symbol f1: -X_1 >= 0 /\ X_1 >= 0 For symbol f4: -X_2 >= 0 /\ X_1 - X_2 >= 0 /\ X_1 >= 0 This yielded the following problem: 4: T: (?, 1) f4(a, b, c) -> f4(1, b, d) [ -b >= 0 /\ a - b >= 0 /\ a >= 0 ] (1, 1) f1(a, b, c) -> f4(a, b, d) [ -a >= 0 /\ a >= 0 /\ 0 >= b ] (b, 1) f1(a, b, c) -> f1(a, b - 1, d) [ -a >= 0 /\ a >= 0 /\ b >= 1 ] (1, 1) f0(a, b, c) -> f1(0, b, c) start location: f0 leaf cost: 0 By chaining the transition f1(a, b, c) -> f4(a, b, d) [ -a >= 0 /\ a >= 0 /\ 0 >= b ] with all transitions in problem 4, the following new transition is obtained: f1(a, b, c) -> f4(1, b, d') [ -a >= 0 /\ a >= 0 /\ 0 >= b /\ -b >= 0 /\ a - b >= 0 ] We thus obtain the following problem: 5: T: (1, 2) f1(a, b, c) -> f4(1, b, d') [ -a >= 0 /\ a >= 0 /\ 0 >= b /\ -b >= 0 /\ a - b >= 0 ] (?, 1) f4(a, b, c) -> f4(1, b, d) [ -b >= 0 /\ a - b >= 0 /\ a >= 0 ] (b, 1) f1(a, b, c) -> f1(a, b - 1, d) [ -a >= 0 /\ a >= 0 /\ b >= 1 ] (1, 1) f0(a, b, c) -> f1(0, b, c) start location: f0 leaf cost: 0 By chaining the transition f1(a, b, c) -> f4(1, b, d') [ -a >= 0 /\ a >= 0 /\ 0 >= b /\ -b >= 0 /\ a - b >= 0 ] with all transitions in problem 5, the following new transition is obtained: f1(a, b, c) -> f4(1, b, d) [ -a >= 0 /\ a >= 0 /\ 0 >= b /\ -b >= 0 /\ a - b >= 0 /\ -b + 1 >= 0 /\ 1 >= 0 ] We thus obtain the following problem: 6: T: (1, 3) f1(a, b, c) -> f4(1, b, d) [ -a >= 0 /\ a >= 0 /\ 0 >= b /\ -b >= 0 /\ a - b >= 0 /\ -b + 1 >= 0 /\ 1 >= 0 ] (?, 1) f4(a, b, c) -> f4(1, b, d) [ -b >= 0 /\ a - b >= 0 /\ a >= 0 ] (b, 1) f1(a, b, c) -> f1(a, b - 1, d) [ -a >= 0 /\ a >= 0 /\ b >= 1 ] (1, 1) f0(a, b, c) -> f1(0, b, c) start location: f0 leaf cost: 0 By chaining the transition f1(a, b, c) -> f4(1, b, d) [ -a >= 0 /\ a >= 0 /\ 0 >= b /\ -b >= 0 /\ a - b >= 0 /\ -b + 1 >= 0 /\ 1 >= 0 ] with all transitions in problem 6, the following new transition is obtained: f1(a, b, c) -> f4(1, b, d') [ -a >= 0 /\ a >= 0 /\ 0 >= b /\ -b >= 0 /\ a - b >= 0 /\ -b + 1 >= 0 /\ 1 >= 0 ] We thus obtain the following problem: 7: T: (1, 4) f1(a, b, c) -> f4(1, b, d') [ -a >= 0 /\ a >= 0 /\ 0 >= b /\ -b >= 0 /\ a - b >= 0 /\ -b + 1 >= 0 /\ 1 >= 0 ] (?, 1) f4(a, b, c) -> f4(1, b, d) [ -b >= 0 /\ a - b >= 0 /\ a >= 0 ] (b, 1) f1(a, b, c) -> f1(a, b - 1, d) [ -a >= 0 /\ a >= 0 /\ b >= 1 ] (1, 1) f0(a, b, c) -> f1(0, b, c) start location: f0 leaf cost: 0 By chaining the transition f1(a, b, c) -> f4(1, b, d') [ -a >= 0 /\ a >= 0 /\ 0 >= b /\ -b >= 0 /\ a - b >= 0 /\ -b + 1 >= 0 /\ 1 >= 0 ] with all transitions in problem 7, the following new transition is obtained: f1(a, b, c) -> f4(1, b, d) [ -a >= 0 /\ a >= 0 /\ 0 >= b /\ -b >= 0 /\ a - b >= 0 /\ -b + 1 >= 0 /\ 1 >= 0 ] We thus obtain the following problem: 8: T: (1, 5) f1(a, b, c) -> f4(1, b, d) [ -a >= 0 /\ a >= 0 /\ 0 >= b /\ -b >= 0 /\ a - b >= 0 /\ -b + 1 >= 0 /\ 1 >= 0 ] (?, 1) f4(a, b, c) -> f4(1, b, d) [ -b >= 0 /\ a - b >= 0 /\ a >= 0 ] (b, 1) f1(a, b, c) -> f1(a, b - 1, d) [ -a >= 0 /\ a >= 0 /\ b >= 1 ] (1, 1) f0(a, b, c) -> f1(0, b, c) start location: f0 leaf cost: 0 By chaining the transition f1(a, b, c) -> f4(1, b, d) [ -a >= 0 /\ a >= 0 /\ 0 >= b /\ -b >= 0 /\ a - b >= 0 /\ -b + 1 >= 0 /\ 1 >= 0 ] with all transitions in problem 8, the following new transition is obtained: f1(a, b, c) -> f4(1, b, d') [ -a >= 0 /\ a >= 0 /\ 0 >= b /\ -b >= 0 /\ a - b >= 0 /\ -b + 1 >= 0 /\ 1 >= 0 ] We thus obtain the following problem: 9: T: (1, 6) f1(a, b, c) -> f4(1, b, d') [ -a >= 0 /\ a >= 0 /\ 0 >= b /\ -b >= 0 /\ a - b >= 0 /\ -b + 1 >= 0 /\ 1 >= 0 ] (?, 1) f4(a, b, c) -> f4(1, b, d) [ -b >= 0 /\ a - b >= 0 /\ a >= 0 ] (b, 1) f1(a, b, c) -> f1(a, b - 1, d) [ -a >= 0 /\ a >= 0 /\ b >= 1 ] (1, 1) f0(a, b, c) -> f1(0, b, c) start location: f0 leaf cost: 0 By chaining the transition f1(a, b, c) -> f4(1, b, d') [ -a >= 0 /\ a >= 0 /\ 0 >= b /\ -b >= 0 /\ a - b >= 0 /\ -b + 1 >= 0 /\ 1 >= 0 ] with all transitions in problem 9, the following new transition is obtained: f1(a, b, c) -> f4(1, b, d) [ -a >= 0 /\ a >= 0 /\ 0 >= b /\ -b >= 0 /\ a - b >= 0 /\ -b + 1 >= 0 /\ 1 >= 0 ] We thus obtain the following problem: 10: T: (1, 7) f1(a, b, c) -> f4(1, b, d) [ -a >= 0 /\ a >= 0 /\ 0 >= b /\ -b >= 0 /\ a - b >= 0 /\ -b + 1 >= 0 /\ 1 >= 0 ] (?, 1) f4(a, b, c) -> f4(1, b, d) [ -b >= 0 /\ a - b >= 0 /\ a >= 0 ] (b, 1) f1(a, b, c) -> f1(a, b - 1, d) [ -a >= 0 /\ a >= 0 /\ b >= 1 ] (1, 1) f0(a, b, c) -> f1(0, b, c) start location: f0 leaf cost: 0 By chaining the transition f1(a, b, c) -> f4(1, b, d) [ -a >= 0 /\ a >= 0 /\ 0 >= b /\ -b >= 0 /\ a - b >= 0 /\ -b + 1 >= 0 /\ 1 >= 0 ] with all transitions in problem 10, the following new transition is obtained: f1(a, b, c) -> f4(1, b, d') [ -a >= 0 /\ a >= 0 /\ 0 >= b /\ -b >= 0 /\ a - b >= 0 /\ -b + 1 >= 0 /\ 1 >= 0 ] We thus obtain the following problem: 11: T: (1, 8) f1(a, b, c) -> f4(1, b, d') [ -a >= 0 /\ a >= 0 /\ 0 >= b /\ -b >= 0 /\ a - b >= 0 /\ -b + 1 >= 0 /\ 1 >= 0 ] (?, 1) f4(a, b, c) -> f4(1, b, d) [ -b >= 0 /\ a - b >= 0 /\ a >= 0 ] (b, 1) f1(a, b, c) -> f1(a, b - 1, d) [ -a >= 0 /\ a >= 0 /\ b >= 1 ] (1, 1) f0(a, b, c) -> f1(0, b, c) start location: f0 leaf cost: 0 By chaining the transition f1(a, b, c) -> f4(1, b, d') [ -a >= 0 /\ a >= 0 /\ 0 >= b /\ -b >= 0 /\ a - b >= 0 /\ -b + 1 >= 0 /\ 1 >= 0 ] with all transitions in problem 11, the following new transition is obtained: f1(a, b, c) -> f4(1, b, d) [ -a >= 0 /\ a >= 0 /\ 0 >= b /\ -b >= 0 /\ a - b >= 0 /\ -b + 1 >= 0 /\ 1 >= 0 ] We thus obtain the following problem: 12: T: (1, 9) f1(a, b, c) -> f4(1, b, d) [ -a >= 0 /\ a >= 0 /\ 0 >= b /\ -b >= 0 /\ a - b >= 0 /\ -b + 1 >= 0 /\ 1 >= 0 ] (?, 1) f4(a, b, c) -> f4(1, b, d) [ -b >= 0 /\ a - b >= 0 /\ a >= 0 ] (b, 1) f1(a, b, c) -> f1(a, b - 1, d) [ -a >= 0 /\ a >= 0 /\ b >= 1 ] (1, 1) f0(a, b, c) -> f1(0, b, c) start location: f0 leaf cost: 0 By chaining the transition f1(a, b, c) -> f4(1, b, d) [ -a >= 0 /\ a >= 0 /\ 0 >= b /\ -b >= 0 /\ a - b >= 0 /\ -b + 1 >= 0 /\ 1 >= 0 ] with all transitions in problem 12, the following new transition is obtained: f1(a, b, c) -> f4(1, b, d') [ -a >= 0 /\ a >= 0 /\ 0 >= b /\ -b >= 0 /\ a - b >= 0 /\ -b + 1 >= 0 /\ 1 >= 0 ] We thus obtain the following problem: 13: T: (1, 10) f1(a, b, c) -> f4(1, b, d') [ -a >= 0 /\ a >= 0 /\ 0 >= b /\ -b >= 0 /\ a - b >= 0 /\ -b + 1 >= 0 /\ 1 >= 0 ] (?, 1) f4(a, b, c) -> f4(1, b, d) [ -b >= 0 /\ a - b >= 0 /\ a >= 0 ] (b, 1) f1(a, b, c) -> f1(a, b - 1, d) [ -a >= 0 /\ a >= 0 /\ b >= 1 ] (1, 1) f0(a, b, c) -> f1(0, b, c) start location: f0 leaf cost: 0 By chaining the transition f1(a, b, c) -> f4(1, b, d') [ -a >= 0 /\ a >= 0 /\ 0 >= b /\ -b >= 0 /\ a - b >= 0 /\ -b + 1 >= 0 /\ 1 >= 0 ] with all transitions in problem 13, the following new transition is obtained: f1(a, b, c) -> f4(1, b, d) [ -a >= 0 /\ a >= 0 /\ 0 >= b /\ -b >= 0 /\ a - b >= 0 /\ -b + 1 >= 0 /\ 1 >= 0 ] We thus obtain the following problem: 14: T: (1, 11) f1(a, b, c) -> f4(1, b, d) [ -a >= 0 /\ a >= 0 /\ 0 >= b /\ -b >= 0 /\ a - b >= 0 /\ -b + 1 >= 0 /\ 1 >= 0 ] (?, 1) f4(a, b, c) -> f4(1, b, d) [ -b >= 0 /\ a - b >= 0 /\ a >= 0 ] (b, 1) f1(a, b, c) -> f1(a, b - 1, d) [ -a >= 0 /\ a >= 0 /\ b >= 1 ] (1, 1) f0(a, b, c) -> f1(0, b, c) start location: f0 leaf cost: 0 By chaining the transition f1(a, b, c) -> f4(1, b, d) [ -a >= 0 /\ a >= 0 /\ 0 >= b /\ -b >= 0 /\ a - b >= 0 /\ -b + 1 >= 0 /\ 1 >= 0 ] with all transitions in problem 14, the following new transition is obtained: f1(a, b, c) -> f4(1, b, d') [ -a >= 0 /\ a >= 0 /\ 0 >= b /\ -b >= 0 /\ a - b >= 0 /\ -b + 1 >= 0 /\ 1 >= 0 ] We thus obtain the following problem: 15: T: (1, 12) f1(a, b, c) -> f4(1, b, d') [ -a >= 0 /\ a >= 0 /\ 0 >= b /\ -b >= 0 /\ a - b >= 0 /\ -b + 1 >= 0 /\ 1 >= 0 ] (?, 1) f4(a, b, c) -> f4(1, b, d) [ -b >= 0 /\ a - b >= 0 /\ a >= 0 ] (b, 1) f1(a, b, c) -> f1(a, b - 1, d) [ -a >= 0 /\ a >= 0 /\ b >= 1 ] (1, 1) f0(a, b, c) -> f1(0, b, c) start location: f0 leaf cost: 0 By chaining the transition f1(a, b, c) -> f4(1, b, d') [ -a >= 0 /\ a >= 0 /\ 0 >= b /\ -b >= 0 /\ a - b >= 0 /\ -b + 1 >= 0 /\ 1 >= 0 ] with all transitions in problem 15, the following new transition is obtained: f1(a, b, c) -> f4(1, b, d) [ -a >= 0 /\ a >= 0 /\ 0 >= b /\ -b >= 0 /\ a - b >= 0 /\ -b + 1 >= 0 /\ 1 >= 0 ] We thus obtain the following problem: 16: T: (1, 13) f1(a, b, c) -> f4(1, b, d) [ -a >= 0 /\ a >= 0 /\ 0 >= b /\ -b >= 0 /\ a - b >= 0 /\ -b + 1 >= 0 /\ 1 >= 0 ] (?, 1) f4(a, b, c) -> f4(1, b, d) [ -b >= 0 /\ a - b >= 0 /\ a >= 0 ] (b, 1) f1(a, b, c) -> f1(a, b - 1, d) [ -a >= 0 /\ a >= 0 /\ b >= 1 ] (1, 1) f0(a, b, c) -> f1(0, b, c) start location: f0 leaf cost: 0 By chaining the transition f1(a, b, c) -> f4(1, b, d) [ -a >= 0 /\ a >= 0 /\ 0 >= b /\ -b >= 0 /\ a - b >= 0 /\ -b + 1 >= 0 /\ 1 >= 0 ] with all transitions in problem 16, the following new transition is obtained: f1(a, b, c) -> f4(1, b, d') [ -a >= 0 /\ a >= 0 /\ 0 >= b /\ -b >= 0 /\ a - b >= 0 /\ -b + 1 >= 0 /\ 1 >= 0 ] We thus obtain the following problem: 17: T: (1, 14) f1(a, b, c) -> f4(1, b, d') [ -a >= 0 /\ a >= 0 /\ 0 >= b /\ -b >= 0 /\ a - b >= 0 /\ -b + 1 >= 0 /\ 1 >= 0 ] (?, 1) f4(a, b, c) -> f4(1, b, d) [ -b >= 0 /\ a - b >= 0 /\ a >= 0 ] (b, 1) f1(a, b, c) -> f1(a, b - 1, d) [ -a >= 0 /\ a >= 0 /\ b >= 1 ] (1, 1) f0(a, b, c) -> f1(0, b, c) start location: f0 leaf cost: 0 By chaining the transition f1(a, b, c) -> f4(1, b, d') [ -a >= 0 /\ a >= 0 /\ 0 >= b /\ -b >= 0 /\ a - b >= 0 /\ -b + 1 >= 0 /\ 1 >= 0 ] with all transitions in problem 17, the following new transition is obtained: f1(a, b, c) -> f4(1, b, d) [ -a >= 0 /\ a >= 0 /\ 0 >= b /\ -b >= 0 /\ a - b >= 0 /\ -b + 1 >= 0 /\ 1 >= 0 ] We thus obtain the following problem: 18: T: (1, 15) f1(a, b, c) -> f4(1, b, d) [ -a >= 0 /\ a >= 0 /\ 0 >= b /\ -b >= 0 /\ a - b >= 0 /\ -b + 1 >= 0 /\ 1 >= 0 ] (?, 1) f4(a, b, c) -> f4(1, b, d) [ -b >= 0 /\ a - b >= 0 /\ a >= 0 ] (b, 1) f1(a, b, c) -> f1(a, b - 1, d) [ -a >= 0 /\ a >= 0 /\ b >= 1 ] (1, 1) f0(a, b, c) -> f1(0, b, c) start location: f0 leaf cost: 0 By chaining the transition f1(a, b, c) -> f4(1, b, d) [ -a >= 0 /\ a >= 0 /\ 0 >= b /\ -b >= 0 /\ a - b >= 0 /\ -b + 1 >= 0 /\ 1 >= 0 ] with all transitions in problem 18, the following new transition is obtained: f1(a, b, c) -> f4(1, b, d') [ -a >= 0 /\ a >= 0 /\ 0 >= b /\ -b >= 0 /\ a - b >= 0 /\ -b + 1 >= 0 /\ 1 >= 0 ] We thus obtain the following problem: 19: T: (1, 16) f1(a, b, c) -> f4(1, b, d') [ -a >= 0 /\ a >= 0 /\ 0 >= b /\ -b >= 0 /\ a - b >= 0 /\ -b + 1 >= 0 /\ 1 >= 0 ] (?, 1) f4(a, b, c) -> f4(1, b, d) [ -b >= 0 /\ a - b >= 0 /\ a >= 0 ] (b, 1) f1(a, b, c) -> f1(a, b - 1, d) [ -a >= 0 /\ a >= 0 /\ b >= 1 ] (1, 1) f0(a, b, c) -> f1(0, b, c) start location: f0 leaf cost: 0 Complexity upper bound ? Time: 1.210 sec (SMT: 1.129 sec)